Kedisiplinan Anak dalam Melaksanakan Shalat Berjama’ah di Panti Asuhan Aisyiyah Barulak Kecamatan Tanjung Baru Kabupaten Tanah Datar - Nurjanah, Nila; Arifmiboy, Arifmiboy; Salmiwati, Salmiwati; Junaidi, Junaidi (Lembaga Yasin AlSys, 2023)
The main problem in this study is based on the results of observations and interviews which found that there are foster children who are still lacking in discipline in carrying out congregational prayers properly and do not carry out activities according to the existing daily schedule. This also makes the implementation of activities in the orphanage not optimal. The purpose of this study is to determine the discipline of children in carrying out the obligatory prayers in congregation at the Aisyiyah Barulak orphanage, Tanjung Baru District, Tanah Datar Regency.This research is descriptive qualitative in nature, namely a method that describes the conditions that occur in the field in the form of words or not in the form of numbers. The informants in this study consisted of key informants, namely foster children at the Aisyiyah Barulak Orphanage, Tanjung Baru District, Tanah Datar Regency, and supporting informants, namely foster mothers at the Aisyiyah Barulak Orphanage, Tnjunhg Baru District, Tanah Datar Regency. Data was collected by conducting observation and interview guidelines. Data processing techniques use descriptive qualitative analysis and techniques to test the validity of the data.Based on the results of research at the Aisyiyah Barulak Orphanage, Tanjung Baru District, Tanah Datar Regency, the discipline of children in carrying out congregational prayers. As a foster mother in disciplining children for congregational prayers by guiding children, accompanying, advising children who do not go to congregational prayers and providing prayer equipment for foster children. Furthermore, foster children have been given a daily schedule that must be carried out every day. The results of this study indicate that children lack discipline in carrying out congregational prayers at the Aisyiyah Barulak Orphanage in Tanah Datar Regency because there is no written sanction from the orphanage for congregational prayers, the distance and time are quite far from the orphanage to the mosque, the lack of guidance from the orphanage caretaker. , prayer equipment and recitation of the priest's prayer verses which are long enough to make children lazy to go to congregational prayers to the mosque